A Hidden Pigment, A Damaged Joint: The Ochronotic Knee - A Case Report - Riaz, Saad; Ijaz, Osama; Farooq, Talha (Journal of Rawalpindi Medical College, 2026)
Ochronotic arthropathy (alkaptonuria) is a rare hereditary disorder that poses a diagnostic dilemma. It is usually diagnosed perioperatively or by conducting investigations based on perioperative findings in the postoperative period, followed by retrospective analysis. This report discusses a case of a 37-year-old male who presented with bilateral knee pain. Radiological studies were indicative of grade III osteoarthritis but perioperatively black pigmentation was noted. Backtracking revealed it to be a case of alkaptonuria. This typically presents as early-onset osteoarthritis involving major joints like the knee, hip, shoulder, and spine. Orthopedic surgeons should have an inquisitive mind and keep this as their differential diagnosis while dealing with young patients with similar symptoms to avoid surprises during surgery. Our study aims to increase understanding of this condition for effective management and improving functional outcomes. Keywords: Alkaptonuria, Ochronosis, Osteoarthritis, Rare Disease